Properties of locally produced clay bricks (Laboratory Test) - Louis, Jonathan Philip (Universiti Malaysia Sarawak, (UNIMAS), 2001)
There is a need to examine the strength of bricks, especially in load bearing construction. The main objective of this research is to determine the strength of locally produced clay bricks, in Sarawak. To achieve the objective, several experimental works was conducted. Tests such as measurement of dimension, compressive strength of single unit, prism test, flexural test and mortar cubes test. The tests are corresponding to BS 5628: part 1 and BS 3921: 1985. Besides that, BIA Technical Notes, ASTM and former student research were used as a method and results comparison. Finally, it can be conclude that, locally produced clay bricks were complying with the standard mentioned above and suitable for load bearing construction. The research stress on the results obtained from the test conducted in lab and recommendations were suggested for future research.